Toxicity and gastric tolerance of essential oils from cymbopogon citratus, ocimum gratissimum and ocimum basilicum in wistar rats - Fandohan, P.; Gnonlonfin, G.J.B.; Laleye, A.; Gbenou, J.D.; Darboux, R.; Moudachirou, M. (Elsevier, 2008)
Oils of Cymbopogon citratus, Ocimum gratissimum and Ocimum basilicum are widely used for their medicinal properties, and as food flavours and perfumes. Recently in a study in West Africa, these oils have been recommended to combat Fusarium verticillioides and subsequent fumonisin contamination in stored maize, but their toxicological profile was not investigated. The current study was undertaken to provide data on acute and subacute toxicity as well as on gastric tolerance of these oils in rat. For this purpose, the oils were given by gavage to Wistar rats for 14 consecutive days. The animals were observed daily for their general behaviour and survival, and their visceral organs such as stomach and liver were taken after sacrifice for histological analyses. A dose-dependent effect of the tested oils was observed during the study. Applied at doses generally higher than 1500 mg/kg body weight, the oils caused significant functional damages to stomach and liver of rat. Unlike the other oils, administration of O. gratissimum oil did not result in adverse effects in rat liver at the tested doses. The no observed adverse effect level (NOAEL) of the tested oils has been established. The three tested oils can be considered as safe to human when applied on stored maize at recommended concentrations.